2021
DOI: 10.1016/j.ejvs.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Microbubbles and Ultrasound Accelerated Thrombolysis for Peripheral Arterial Occlusions: The Outcomes of a Single Arm Phase II Trial

Abstract: WHAT THIS PAPER ADDSSince the introduction of thrombolysis in the 1990s, significant changes have been made in thrombolytic agents and administration techniques. Numerous methods, such as ultrasound assisted thrombolysis, have been investigated to improve the results of the technique. The efficacy and associated complication rates have, nevertheless, remained unchanged. The aim of this study was to investigate an experimental ultrasound technique combined with microbubbles as a potential accelerator of convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…13,14 The potential use of MBs combined with US and thrombolytic therapy simultaneously shows to be promising in previous (pre-)clinical studies. 9,10,15 The efficacy of thrombolysis might, however, be further improved by intraarterial administration of MBs through an endovascular US catheter. Higher concentrations of MBs within the clot may enlarge the cavitation response, which will ultimately accelerate thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The potential use of MBs combined with US and thrombolytic therapy simultaneously shows to be promising in previous (pre-)clinical studies. 9,10,15 The efficacy of thrombolysis might, however, be further improved by intraarterial administration of MBs through an endovascular US catheter. Higher concentrations of MBs within the clot may enlarge the cavitation response, which will ultimately accelerate thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“… 9 More recently, we have demonstrated the clinical safety and applicability of CEST in the MUST (Microbubbles and UltraSound-accelerated Thrombolysis for peripheral arterial occlusions) trial, including 20 patients with peripheral arterial occlusion. 10 This novel technique at present has some limitations such as the need for external application of US, which exhibits an interoperator variability that may negatively affect the cavitation effect. Another limitation is that intravenous administration of MBs primarily induces cavitation on the surface of the thrombus and not directly into the thrombus until microchannels are formed or partial reperfusion is ensured.…”
Section: Introductionmentioning
confidence: 99%
“…Indirect thrombolytic effects of TUS mainly enhance the effectiveness of thrombolytic drugs. In addition, ultrasound can directly dissolve the thrombus through its special physical and chemical properties (Cao et al, 2021;Doelare et al, 2021;Mei and Zhang, 2021). The main thrombolytic effects of TUS are summarized as follows.…”
Section: Thrombolytic Effect Of Transcranial Ultrasound Stimulationmentioning
confidence: 99%
“…Some studies have shown that ultrasound combined with microbubbles can enhance the thrombolytic effect of CDT. 9,10 The most important aspect of this treatment modality is that it can reduce the dosage of thrombolytic drugs, which is beneficial for patients at high risk of bleeding who are strictly limited to thrombolytic therapy. Several studies have revealed that the mechanism of ultrasound combined with microbubbles to enhance thrombolysis is cavitation-mediated acoustic radiation, microjet, and microstreaming, which facilitates enzymatic degradation and mechanical destruction of thrombus, [11][12][13] and these responses are mainly regulated by ultrasound parameters and microbubble.…”
mentioning
confidence: 99%
“…Recently, sonothrombolysis or ultrasound thrombolysis has emerged as a promising method for thrombolytic therapy. Some studies have shown that ultrasound combined with microbubbles can enhance the thrombolytic effect of CDT 9,10 . The most important aspect of this treatment modality is that it can reduce the dosage of thrombolytic drugs, which is beneficial for patients at high risk of bleeding who are strictly limited to thrombolytic therapy.…”
mentioning
confidence: 99%